Model for Educational Game Using Natural User Interface - Azrulhizam Shapi’i; Sychol Ghulam (International Journal of Computer Games Technology)
Natural User Interface (NUI) is a new approach that has become increasingly popular in Human-Computer Interaction (HCI). The use of this technology is widely used in almost all sectors, including the field of education. In recent years, there are a lot of educational games using NUI technology in the market such as Kinect game. Kinect is a sensor that can recognize body movements, postures, and voices in three dimensions. It enables users to control and interact with game without the need of using game controller. However, the contents of most existing Kinect games do not follow the standard curriculum in classroom, thus making it do not fully achieve the learning objectives. Hence, this research proposes a design model as a guideline in designing educational game using NUI. A prototype has been developed as one of the objectives in this study. The prototype is based on proposed model to ensure and assess the effectiveness of the model. The outcomes of this study conclude that the proposed model contributed to the design method for the development of the educational game using NUI. Furthermore, evaluation results of the prototype show a good response from participant and in line with the standard curriculum.